2022
DOI: 10.1016/j.jds.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties evaluation of rapid sintered translucent zirconia with two dental colorimeters

Abstract: Background/purpose The efficient rapid sintering technique has employed to dental zirconia ceramics for shortening the fabrication time of zirconia restorations. The purpose was to compare the optical properties of two generations of rapid sintered translucent zirconia using two dental colorimeters. Materials and methods Two generations of translucent zirconia ceramics, 3 mol% yttria-tetragonal zirconia polycrystal (3Y-TZP): Copran Zr-i Ultra-T (UT) and Cercon HT (HT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…Numerous studies have been conducted for improving the aesthetics, strength, and toughness of zirconia [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Grain boundaries, pores, the presence of secondary phases, and light scattered by rough surfaces have been reported to reduce the translucency of zirconia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted for improving the aesthetics, strength, and toughness of zirconia [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Grain boundaries, pores, the presence of secondary phases, and light scattered by rough surfaces have been reported to reduce the translucency of zirconia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Translucency (TP) was not significantly influenced by the sintering method - highest TP was Kat. UTML CS (25.40 ± 0.48)/ lowest TP Zpex Smile SS (15.34 ± 0.54) Liu 2022 [ 43 ] translucency TP of different sintering using two colorimeters 3Y-PSZ : Cercon HT (HT),Copran Zr-i Ultra-T (UT) 5Y-PSZ: Cercon xt (XT), 5 Conventional and rapid sintering according to the manufacturers’ instructions 0.5, 0.8, and 1.2 mm Vita Easy-shade V, zahinfabrik,Germany (Vita) Shadepilot,DeguDent, GmbH, Germany (DD) Results were shown in figures TP values of the CS, RS group were nearly, except XT group with DD. XT was significantly highest TP Vafaei 2022 [ 44 ] translucency parameter (TP) with various sintering temperature 5Y-PSZ : -White Peaks Symphony (WPS) -e. max ZirCAD (IEZ) 10 at 1530, 1500, or 1440 °C with 17 °C/min heating rate for 2 h 1 mm digital camera (Canon EOS 6D 20.2MP) (TP) WPS 1440: 9.25 ± 0.99, 1500: 11.33 ± 0.68, at 1530: 13.34 ± 0.83 IEZ 1440: 8.12 ± 0.47, 1500: 9.32 ± 0.25, at 1530: 10.65 ± 0.48 Park 2022 [ 45 ] translucency parameter (TP) 5Y-PSZ : Rainbow High Shine, 4Y-PSZ: Rainbow Shine, 3Y-PSZ :RainbowShade, lithium disilicate 10 sintered according to the manufacturers’ instructions 0.8 mm and 1.5 mm spectrophotometer (SpectroShade Micro; MHT Optic Research AG) TP at 0.8 mm: 3Y-TZP: 13.32 ± 0.32 4Y TZP: 14.12 ± 0.18 5Y TZP: 16.47 ± 0.39 Lithium disilicate 19.17 ± 0.29 TP at 1.5 mm: 3Y-TZP: 10.55 ± 0.14 4Y TZP: 11.89 ± 0.26 5Y TZP: 14.13 ± 0.12 Lithium disilicate: 14.20 ± 0.32 Kongkiatkamon.2022 [ 46 ] Effect of speed sintering on translucency parameter (TP) 5Y-PSZ: Katana STML 15 RS: regular sintering for 2 h, at 1550 ◦C SS: speed sintering for16 min, at1560 ◦C 1.23 mm ...…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggested speed sintering procedures resulted in a reduction in translucency. that further investigations are necessary to find out the effect of different sintering methods on various YSZ [ 42 , 43 , 52 , 53 , 56 , 65 , 66 , 75 ]. Salah 2023 found that superspeed sintering for 10 min significantly reduced translucency and resulted in a greater change in color [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Vita Easyshade V is designed for in-vivo color measurements, it has also been used for in-vitro measurements in many studies and its accuracy and reliability have been demonstrated. 8,13,15,22,23 CIELAB color difference formula (ΔE) has been used to evaluate color changes in dental restorative materials. However, in the last decade, researchers have been reporting color changes using the CIEDE2000 color change formula (ΔE 00 ), which has been proven to be more accurate in the visual perception of color change.…”
Section: Discussionmentioning
confidence: 99%